Extensive secretion of phenolic acids and fatty acids facilitates rhizosphere pH regulation in halophyte Puccinellia tenuiflora under alkali stress. Issue 2 (18th April 2022) - Li, Hong; Xu, Chenyang; Han, Lei; Li, Changyou; Xiao, Binbin; Wang, Huan; Yang, Chunwu
Abstract: Puccinellia tenuiflora is a forage grass with high nutritional value that is an extreme alkali‐tolerant halophyte: it can survive at pH 10–11. Root secretion is perceived as a major plant alkali tolerance mechanism. In the present study, we applied a widely targeted metabolomic approach to identify and quantify the root exudates of P. tenuiflora under alkali stress. We also surveyed the transcriptional and metabolic profiling of P. tenuiflora roots under salt (96‐mM Na +, pH 6.8) and alkali (96‐mM Na +, pH 9.6) stresses to reveal the biological processes mediating root secretion. In P. tenuiflora plants, 493 root exudates were detected under control conditions, 544 root exudates under salt stress conditions, and 607 root exudates under alkali stress conditions. Salt‐stressed plants and alkali‐stressed plants shared 64 root exudates, and 60 root exudates were unique to alkali‐stressed plants. The secretion rate of 56 phenolic acids, 43 fatty acids, and 9 organic acids was faster in alkali‐stressed roots than in control and salt‐stressed roots. In P. tenuiflora roots, alkali stress enhanced the accumulation of 23 phenolic acids, five organic acids, and only one fatty acid. In addition, transcriptomic analysis revealed that alkali stress upregulated glycolysis and phenylpropanoid biosynthesis pathways in P. tenuiflora roots. Taken together, extensive secretion of phenolic acids and fatty acids promotes rhizosphere pH regulation of P. tenuiflora under alkali stress, which contributes to its strong alkali tolerance. The root secretion of P. tenuiflora upon alkali stress is highly organized. Enhanced glycolysis, phenylpropanoid biosynthesis, and organic acid synthesis in the roots provide more reducing power and carbon source for the root secretion process of alkali‐stressed P. tenuiflora .